Prevalência e fatores associados às alterações neurocognitivas em pessoas vivendo com HIV/AIDS - Lamas, Daniela Pereira [UNIFESP] (2018)
Introduction: It is now known that human immunodeficiency virus (HIV) is the main responsible for the development of neurocognitive disorder in individuals under 40 years. The development of antiretrovirals, the understanding of the pathophysiology of the disease and the search for the better quality of life of the patient living with HIV allowed the chronic evolution of the disease. Increasingly, HIV-related dementia (HAD) has been observed, whose treatment and understanding have become fundamental for the care of these patients. Objectives: The objective of this study was to determine the prevalence and main factors associated with HAD in an outpatient service in Brazil. Methods: 134 Patients living with HIV were evaluated, and two screening tests were performed: Minimental for the evaluation of cortical dementia and the HIV international dementia scale for the evaluation of subcortical dementia. Results: In this study, 29 patients with signs of HIV-related dementia (Prevalence: 21.6% [95% CI: 15.0-29.6]) were observed. The factors independently associated with HAD in our study, with statistical significance, were: older age (RPaj 1.05, 95% CI 1.00-1.09, p = 0.033), lower nadir of TCD4 + (RPaj 0.988, 95% CI, 0.996-0.999, p = 0.030) detectable serum HIV viral load time greater than two years (RPaj 2.35, CI% 1.27-4.33, p = 0.006). Conclusions: The prevalence of HAD in our study was like national and international data. Diagnosis and early treatment with antiretrovirals are very important to minimize the occurrence of cognitive changes in PLHIV, particularly in patients with more advanced age.